Sensory Assessment and Physicochemical Properties of Wheat Bread Supplemented with Chia Seeds - Stanisław Kowalski; Anna Mikulec; Henryk Pustkowiak (Polish Journal of Food and Nutrition Sciences)
Quantitative descriptive analysis, consumer acceptability as well as physicochemical characteristics were employed to analyse the effect of ground chia seeds on the texture and quality of wheat bread. Chia seed oil changes and its impact on selected characteristics were determined. The share of chia seeds did not contribute to bread quality deterioration. The addition of 7.5% chia seeds significantly reduced consumer acceptance as well as contributed to the development of undesirable features in the sensory profile, including fatty, rancid, and off-flavour. The share of chia seeds in an amount not exceeding 5% did not deteriorate the overall quality of bread. The composition of fatty acids of bread with chia seeds, especially with their 5 and 7.5% addition, could be valuable from the nutritional point of view. The fatty acid profile of bread with 5 and 7.5% chia seeds was characterised by over 50% higher polyunsaturated fatty acids to saturated fatty acids ratio compared to wheat bread. The n-6/n-3 ratio in the fatty acid profile of wheat bread was 18.77, while in the fatty acid profile of chia seed bread it ranged from 1.42 to 0.67. Oil extracted from bread exhibited better quality features as compared to oil extracted from chia seeds and subjected to the oxidative stability test.